1991
DOI: 10.1002/ccd.1810220305
|View full text |Cite
|
Sign up to set email alerts
|

Cortical blindness after coronary angiography: A rare but reversible complication

Abstract: Transient cortical blindness is a recognized complication after vertebral and cerebral angiography but is a rare event after cardiac angiography. The development of cortical blindness appears to be an adverse reaction to the contrast agent which results in an osmotic disruption of the blood-brain barrier which appears to be selective for the occipital cortex. Patient outcome appears to be generally favorable with return of vision within 24-48 hr. This study describes three patients who had transient cortical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 10 publications
0
40
0
Order By: Relevance
“…1,8,10,[14][15][16]19) The incidence of transient cortical blindness is as high as 1% with cerebral angiography. 5,17) However, the recent introduction of non-ionic contrast materials is considered to have significantly reduced the risk, and this complication has become extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,10,[14][15][16]19) The incidence of transient cortical blindness is as high as 1% with cerebral angiography. 5,17) However, the recent introduction of non-ionic contrast materials is considered to have significantly reduced the risk, and this complication has become extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarises the published CIE cases following cardiac catheterisation with normal head CT findings from 1970 to the present day. To date there have been 16 cases [1-11]. …”
Section: Discussionmentioning
confidence: 99%
“…In most cases of CIE, the prognosis has been excellent, with rapid recovery with supportive management only, usually by use of intravenous hydration and close observation of the patient [1-11], which is recommended in the immediate postprocedural period. In a few cases, anticonvulsants have been used to treat seizures [7, 14, 15] and steroids used to reduce cerebral oedema with no adverse consequences [13].…”
Section: Discussionmentioning
confidence: 99%
“…Fischer-Williams et al reported one case in 12,367 coronary angiographies, an incidence of 0.008% [3] and Kinn et al reported three cases in over 6,000 such procedures, an incidence of 0.05% [4].…”
Section: Introductionmentioning
confidence: 99%